2001
DOI: 10.2337/diacare.24.6.1087
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Nerve Function Is Increasingly Impaired During Puberty in Adolescents With Type 1 Diabetes

Abstract: OBJECTIVE -To evaluate the impact of puberty on peripheral nerve function in adolescents with type 1 diabetes.RESEARCH DESIGN AND METHODS -Of 138 eligible patients with type 1 diabetes, 100 patients (age Ͼ9 years and diabetes duration Ͼ2 years) attending an outpatient diabetes clinic and 100 age-and sex-matched healthy control subjects took part in this cross-sectional study. Peripheral motor and sensory nerve conduction tests, cardiovascular reflex tests on the autonomic nervous system, and measurements of vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 25 publications
3
29
0
1
Order By: Relevance
“…In addition, only a few studies have been performed on NCV in diabetic children, and the reported prevalence of DPN varies greatly among different studies (Table 1) [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, only a few studies have been performed on NCV in diabetic children, and the reported prevalence of DPN varies greatly among different studies (Table 1) [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, numerous studies provide evidence of abnormalities in both peripheral and autonomic nerve function in children and teens with type 1 diabetes [61,62,63,64,65]. Once again, older age, longer duration of diabetes and poorer metabolic control appear to be contributing factors to nerve dysfunction [61, 62]. …”
Section: Microvascular Complicationsmentioning
confidence: 99%
“…Riihimaa et al [61] reported increasing subclinical motor nerve impairment during late puberty and after puberty, and reduced sensory nerve conduction velocity and sensory nerve action potentials in adolescents with type 1 diabetes. Similarly, Abad et al [62] found that symptomatic abnormal cutaneous thermal perception is a common finding in young patients with type 1 diabetes.…”
Section: Microvascular Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the possibility to verifying neuropathic alterations at the time of diabetes mellitus diagnosis, particularly diabetes mellitus type 1 (DM type1) was presented in different studies [1,2]. Previous reports pointed out that acute effects of normalization of blood glucose levels and other metabolic parameters have a direct influence on nerve conduction velocity (NCV), as well as on the nerve structure itself [3]. Hyperglycemia is a significant, but also not the crucial factor, that can lead to blood vessel damage (primarily of capillaries) and hence to the decrease of blood flow in the nerve tissue itself.…”
Section: Introductionmentioning
confidence: 99%